Nutritional impact of partial or complete replacement of clover hay by untreated or biologically treated rice straw and corn stalks on: 1. growth performance and economic evaluation of growing New Zealand (NZW) White rabbits - Omer, Hamed A. A. (2021)
The highest improvement in feed conversion was recorded with rabbits that received diets replaced 33% of berseem hay (BH) by RS or CS, followed by that replaced 66% of BH by RS or CS. There were significantly interactions between biological treatments (T), roughage source (S), and replacement levels (L) (T × S × L) only on ADG. The best fed conversion was realized by rabbits fed diet replaced BH with 33% of RS that are treated by Pleurotus ostreatus (4.05 g DMI/g gain). Rabbits fed 33% biologically treated rice straw with Pleurotus ostreatus showed the highest economic efficiency (179%) followed by rabbits that received 33% of both rice straws treated without Pleurotus ostreatus and rabbits that received corn stalks biologically treated with Trichoderma reesei (161%).